Islamisasi Pantai Utara Jawa: Menelusuri Penyiaran Islam di Tanah Betawi - Jajang Jahroni (Jurnal Lektur Keagamaan, 2016)
This article discusses the early Islamization of Betawi. While the Islamization of Betawi began in the 12 th. century, more intensive attempts did not occur until the 14th. and 15th. centuries. Of particular significance was the arrival of Muslim traders in Sunda Kelapa, the most important port located in the northern part of the current Jakarta. The voyage of Cheng Ho, a Hui Muslim admiral, who visited the city in the early 15th. century, played an important part in the Islamization of northern Java. Some of Cheng Ho’s Muslim fellows decided to stay on in the region, and they subsequently expanded the Islamic proselytization into the interior of West Java. The further step of Islamization of the region was continued by the descendants of Prabu Siliwangi, who converted to Islam. They advocated Islam to the Sundanese people who, at that time, still believed in various pagan traditions. Muslim students returning from the Middle East in the 19th. and 20th. centuries extended this process. They built modern institutions such as madrasa and pesantren reaching out to a large audience in the Muslim ommunity. Keywords: Islamization, Betawi, the 14 th and 15 th centuries, madrasa and pesantren Artikel ini membahas awal Islamisasi di Betawi. Proses ini sebenarnya sudah mulai sejak abad ke-12. Namun usaha yang intensif baru dimulai sejak abad ke-14 dan 15. Ini berhubungan dengan kedatangan para pedagang Muslim yang menguasai Sunda Kelapa, pelabuhan terpenting yang terletak di utara Jakarta sekarang. Kedatangan Cheng Ho, seorang nakhoda Hui Muslim, pada awal abad ke-15 sangatlah penting untuk melakukan ekspansi dakwah ke pedalaman Jawa Barat. Islamisasi be¬rikutnya banyak dilakukan oleh keturunan Prabu Siliwangi, raja Hindu Pajajaran. Merekalah yang mendakwahkan Islam ke suku Sunda yang masih percaya dengan agama pagan Sunda. Selanjutnya, para pelajar yang pulang ke Tanah Air setelah menuntut ilmu di Timur Tengah, Mekkah dan Madinah, melanjutkan proses Islamisasi. Mereka membangun lembaga modern seperti madrasa dan pondok pesantren yang dapat mencapai audiensi masyarakat yang lebih luas. Kata Kunci: Islamisasi, Betawi, Abad ke-14 dan 15, madrasah dan pesantren